The Movie business book - Squire, Jason E. 1948-
In The Movie Business Book, forty of Hollywood's most celebrated producers, directors, screenwriters, agents, lawyers, marketers, distributors, exhibitors, and deal makers reveal the secrets of their trade in personal accounts that are both highly informative and wonderfully entertaining.